A procedure for the design of complex mechanical systems by decomposition. (1st January 1999) - Khorshid, E.; Seireg, A.
The design of many practical mechanical systems usually requires dealing with large-scale problems incorporating different physical phenomena with diverse behavioural constraints that are generally non-linear. This paper presents a generalised procedure to aid the designer in making such problems tractable through appropriate segmentation. Accordingly, the interactions between the different components and parameters become clearer, allowing interactive modelling improvement and design decisions to be made serially with immediate feed back on how they influence the design objective. The procedure also aids the designer in identifying and easily correcting any constraint inconsistency or programming errors. Although the methodology is developed for large-scale systems, simple examples are considered for illustration and good feasible solutions can be obtained without extensive computing effort. There is no guarantee, however, that a global optimum design can be achieved by this approach, although in all the tried cases, the solution was optimum.